2019
DOI: 10.1111/rda.13537
|View full text |Cite
|
Sign up to set email alerts
|

Onset of oestrus and periovulatory events in sheep exposed to 5 and 14 days of CIDR treatment with and without eCG

Abstract: The present study supports that 5‐day short‐term CIDR treatments without administration of eCG are equally effective for inducing oestrus behaviour, preovulatory LH discharge and ovulation in sheep than classical protocols based on 14‐day treatments plus eCG at CIDR withdrawal. However, the implementation of a 5‐day protocol without eCG for fixed‐time artificial insemination would be adapted to a later timing of ovulation (p < .05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…In this sense, the current study evidenced that all the ewes in both groups (eCG and hCG) displayed a similar number of gonadotrophin-responsive (≥3 mm) and preovulatory-sized (≥5 mm) follicles during the early stages of the follicular phase, induced by CIDR removal. In such a follicular phase, follicular development and periovulatory events in sheep treated with eCG were similar to previous works using the same protocol [ 3 , 11 , 12 ]. In brief, all sheep showed final follicular growth and onset of estrous behavior prior to 48 h, and almost all of them (95.2%, if joining both trials) ovulated around 70 h after CIDR removal and showed corpora lutea of good quality (as evaluated on Day 14 after CIDR removal).…”
Section: Discussionsupporting
confidence: 84%
“…In this sense, the current study evidenced that all the ewes in both groups (eCG and hCG) displayed a similar number of gonadotrophin-responsive (≥3 mm) and preovulatory-sized (≥5 mm) follicles during the early stages of the follicular phase, induced by CIDR removal. In such a follicular phase, follicular development and periovulatory events in sheep treated with eCG were similar to previous works using the same protocol [ 3 , 11 , 12 ]. In brief, all sheep showed final follicular growth and onset of estrous behavior prior to 48 h, and almost all of them (95.2%, if joining both trials) ovulated around 70 h after CIDR removal and showed corpora lutea of good quality (as evaluated on Day 14 after CIDR removal).…”
Section: Discussionsupporting
confidence: 84%
“…Currently, such knowledge is giving way to “follicle-focused” protocols [ 15 ]. These protocols consist of short-term progestative treatments (5–7 days), which are equally as effective as long-term protocols for inducing preovulatory events and ovulation [ 16 , 17 ], with even a higher fertility [ 2 , 18 ]. Short-term protocols aim to synchronize estrus and ovulation but also the follicular wave from which the ovulatory follicles arise.…”
Section: Introductionmentioning
confidence: 99%
“…These results were however, different to that observed by Kridli et al (2009), in brown and black faced Awassi ewes. Nonetheless, it appears that the onset of oestrus following oestrus synchronization occasionally depends on the protocol used (Uriol et al, 2019). However, the Namaqua Afrikaner ewes took longer period showing signs of oestrus.…”
Section: Discussionmentioning
confidence: 97%